2019
DOI: 10.1371/journal.pone.0225008
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum leptin and adiponectin concentrations with echocardiographic parameters and pathophysiological states in patients with cardiovascular disease receiving cardiovascular surgery

Abstract: Leptin and adiponectin are important regulators of energy metabolism and body composition. Leptin exerts cardiodepressive effects, whereas adiponectin has cardioprotective effects, but several conflicting findings have been reported. The aim of the present study was to assess the relationship between serum leptin and adiponectin levels and echocardiographic parameters and pathophysiological states in patients with cardiovascular disease (CVD) receiving cardiovascular surgery. A total of 128 patients (79 males,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…Inflammatory cytokines may have little effect on energy metabolism in patients with heart failure up to NYHA functional class III. It has been reported that SMI and leptin are positively correlated in heart failure patients [18], which is consistent with our results (Fig. 3b).…”
Section: Discussion/conclusionsupporting
confidence: 94%
See 1 more Smart Citation
“…Inflammatory cytokines may have little effect on energy metabolism in patients with heart failure up to NYHA functional class III. It has been reported that SMI and leptin are positively correlated in heart failure patients [18], which is consistent with our results (Fig. 3b).…”
Section: Discussion/conclusionsupporting
confidence: 94%
“…Conversely, leptin is secreted from adipocytes to suppress food intake and increase energy metabolism [15,17]. In recent report, serum leptin level had a positive correlation with skeletal muscle volume and skeletal muscle index (SMI) [18] and was expected to have cardioprotective effects [19][20][21]. However, the relationship between leptin and energy metabolism has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients undergoing cardiac surgery, leptin was positively correlated with BMI and fat mass, and negatively with the size of the left atrium and cardiac mass index, while adiponectin was positively correlated with the size of the left atrium and E/e'. (27) According to the authors, it suggests that both markers can participate in cardiac remodeling after cardiovascular surgery and thus impact on the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between adiponectin level and left ventricular systolic and diastolic dysfunction have also been studied by other authors. The inverse association of adiponectin level with LVEF was indicated in elderly men [53] or with LVSF in patients with hypertrophic cardiomyopathy [54], but other studies in patients with HF did not confirm this [55][56][57]. Additional evidence confirms that adiponectin levels are positively correlated with indicators of diastolic dysfunction: left ventricular pressure half-time in patients with hypertrophic cardiomyopathy [58], E/E' ratio in HF patients with metabolic syndrome [55] or CVD patients [57] and DT in CAD patients [59].…”
Section: Adiponectinmentioning
confidence: 97%